العلاقات الدلالية ودورها في انسجام الخطاب الشعري نماذج مختارة من ديوان الشافعي - نصبة، بوبكر; غريبي، العلمي; جميلي، محمد العربي (University of Eloued جامعة الوادي, 2024)
الملخص: يتناول البحث أهم العلاقات الدلالية التي ترتبط بمعيار الانسجام باعتباره مظهرا من مظاهر الترابط النصي ، وتتجلى هذه العلاقات في: السببية، الإجمال/التفصيل، والعموم/الخصوص، وعلاقة العنوان بالخطاب، إضافة إلى علاقات دلالية فرعية مثل :التضاد والترادف والاشتمال والجزء من الكل. وتهدف هذه العلاقات الدلالية إلى تحقيق الاستمرارية الدلالية بين مقاطع الخطاب الشعري ومن ثم تجسيد الوظيفة التواصلية ذات الطابع التداولي الحجاجي . Résumé : فرنسية أو انجلزية The research deals with the most important semantic relationships that are related to the coherence criterion as an aspect of textual coherence. These relationships are manifested in: causality, generality/detail, generality/specificity, and the relationship of the title to the discourse, in addition to sub-semantic relationships such as contrast, synonymy, inclusion, and part of the whole. These semantic relationships aim to achieve semantic continuity between the sections of the poetic discourse, and thus embody the communicative function of an argumentative, interactive nature
811/ 014
Keywords: : الديوان - العلاقات الدلالية - الانسجام - الشافعي; Diwan - semantic relationships - harmony - Al-Shafi’i